Preparation method of composite nano sponge capable of efficiently adsorbing rare earth ions in acidic wastewater as well as product and application of composite nano sponge
By mixing β-cyclodextrin-functionalized polyvinyl alcohol with phosphorylated chitosan, a composite nanosponge that efficiently adsorbs rare earth ions in acidic wastewater was prepared, which solved the problems of poor selectivity and poor acid resistance in the prior art, and achieved the goal of achieving the It can efficiently recover and recycle rare earth ions in acidic wastewater.
Patent Information
- Application Number
- CN202411625360.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-01-17
AI Technical Summary
The existing cyclodextrin nanosponges have poor selectivity, poor acid resistance, low adsorption capacity and may have secondary pollution in the recovery of rare earth ions in acidic wastewater, making it difficult to effectively recover rare earth elements, affecting the environment and resource utilization.
By mixing β-cyclodextrin-functionalized polyvinyl alcohol with phosphorylated chitosan and using citric acid as a crosslinking agent, a composite nanosponge that efficiently adsorbs rare earth ions in acidic wastewater is prepared, using the amino group of chitosan and The characteristics of hydroxyl groups and phosphate groups improve the adsorption performance and stability of the material.
It realizes efficient adsorption of Ce3+ and Tb3+, with adsorption amounts reaching 452.21 mg/g and 442.95 mg/g, removal rates are 70.0% and 56.4%, and is maintained efficient in recycling and regeneration. It is suitable for simulating the recovery of rare earth ions in acid mine water. .
Smart Images

Figure CN119318948A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rare earth ion separation and purification, and relates to a preparation method of a composite nano sponge for efficiently absorbing rare earth ions in acidic waste water, and a product and application thereof. Background Art
[0002] Rare earth is a national strategic resource. Rare earth elements have excellent physical and chemical properties such as magnetism, light, and electricity due to their unique electronic layer structure. They have become the key components of modern scientific and technological products, and play an important role in strategic emerging industries such as new energy vehicles, electronic information, aerospace, national defense and military industry, and high-end equipment manufacturing. They are indispensable core basic materials. In many countries, the supply and demand balance of rare earth elements is becoming a major problem facing the development of high-tech fields and emerging industries. In order to solve this problem, it is urgent to change the current situation where the only supply route for rare earth elements is to obtain them from ores.
[0003] Due to the increasing demand for rare earth elements, the continuous expansion of resource mining and improper waste treatment, some rare earth resources are inevitably discharged into the water environment. Acidic wastewater, represented by acid mine water (AMD), will not only have an adverse impact on the mine ecosystem, but also affect the health of surrounding animals, plants and even humans. Therefore, if rare earth elements can be removed or recovered from acidic wastewater, it will not only change the current situation of a single way to obtain rare earth elements, but also solve the problem of environmental pollution.
[0004] Cyclodextrin nanosponges (CDNSs) are a new type of functional nanomaterial based on cyclodextrin, its derivatives and cross-linking agents. They are hydrophilic and have a three-dimensional network structure. They have high stability at higher temperatures and a wide pH range. They have been used as new adsorbents to remove heavy metal ions, dyes, drug molecules, etc. from wastewater. However, due to the poor selectivity, poor acid resistance, low adsorption capacity and possible secondary pollution of cyclodextrin nanosponges, there are few reports on the use of cyclodextrin nanosponges for the recovery of rare earth ions in acidic wastewater. In order to expand the scope of application of cyclodextrin nanosponges, realize their recovery of rare earth ions in acidic wastewater, and thus change the current situation of a single way to obtain rare earth elements, it is urgent to develop new materials based on cyclodextrin nanosponges. Summary of the invention
[0005] In view of this, one of the objects of the present invention is to provide a method for preparing a composite nanosponge that efficiently adsorbs rare earth ions in acidic wastewater; a second object of the present invention is to provide a composite nanosponge that efficiently adsorbs rare earth ions in acidic wastewater; a third object of the present invention is to provide an application of the composite nanosponge that efficiently adsorbs rare earth ions in acidic wastewater in recovering rare earth ions.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] 1. A method for preparing a composite nanosponge that efficiently absorbs rare earth ions in acidic wastewater, the preparation method being as follows:
[0008] (1) adding β-cyclodextrin to a polyvinyl alcohol aqueous solution, and then stirring to obtain a clear liquid; mixing a sodium hydroxide aqueous solution with dimethyl sulfoxide, and then adding epichlorohydrin to form a mixed liquid; pouring the mixed liquid into the clear liquid, and then reacting at 60 to 65° C. for 3 to 4 hours to obtain a polyvinyl alcohol solution grafted with cyclodextrin, and then adding a citric acid aqueous solution to the polyvinyl alcohol solution grafted with cyclodextrin, and then reacting at 75 to 80° C. for 2 to 3 hours to obtain a reaction solution 1;
[0009] (2) placing phosphorylated chitosan in deionized water, then adding acetic acid until the solution becomes viscous, then adding citric acid aqueous solution, and reacting at 75-80° C. for 3 h to obtain reaction solution 2;
[0010] (3) The reaction solution 1 in step (1) and the reaction solution 2 in step (2) are mixed in a volume ratio of 1:1, and then stirred at room temperature for 0.5 to 1 hour. After the stirring, a 1 mol / L sodium hydroxide aqueous solution is added dropwise to obtain a bead-like material. After standing overnight, the bead-like material is taken out and freeze-dried at -18°C for 16 to 24 hours to obtain a composite nanosponge that efficiently adsorbs rare earth ions in acidic wastewater.
[0011] Preferably, the mass percentage of polyvinyl alcohol in the polyvinyl alcohol aqueous solution in step (1) is 10%; and the mass ratio of polyvinyl alcohol to β-cyclodextrin in the polyvinyl alcohol aqueous solution is 1:0.5.
[0012] Preferably, the concentration of the sodium hydroxide aqueous solution in step (1) is 15% w / v; the volume ratio of the sodium hydroxide aqueous solution, dimethyl sulfoxide and epichlorohydrin is 2:1.25:0.4.
[0013] Preferably, in step (1), the volume ratio of the mixed solution to the clarified solution is 0.3:1; the concentration of the citric acid aqueous solution is 15% w / v; and the volume ratio of the cyclodextrin grafted polyvinyl alcohol solution to the citric acid aqueous solution is 5:1.
[0014] Preferably, the preparation method of the phosphorylated chitosan in step (2) is: placing chitosan in deionized water, adding acetic acid, and then stirring at 25-30° C. to a light yellow translucent solution, then adding phosphoric acid to the light yellow translucent solution, and then reacting at 50-55° C. for 3-3.5 hours to obtain a light brown liquid, then slowly pouring the light brown liquid into anhydrous ethanol to form a precipitate, and the precipitate can be centrifuged and washed with ethanol to obtain phosphorylated chitosan.
[0015] Preferably, the mass volume ratio of the chitosan, deionized water, acetic acid and phosphoric acid is 2.5:20:2:25, g:mL:mL:mL.
[0016] Preferably, in step (2), the mass volume ratio of the phosphorylated chitosan, acetic acid and citric acid aqueous solution is 1:100:1, g:μL:mL; and the concentration of the citric acid aqueous solution is 15% w / v.
[0017] Preferably, the dripping speed in step (3) is 1 drop per second.
[0018] 2. A composite nanosponge for efficiently adsorbing rare earth ions in acidic wastewater prepared according to the preparation method.
[0019] 3. Application of the composite nanosponge for efficiently adsorbing rare earth ions in acidic wastewater in recovering rare earth ions.
[0020] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing a composite nanosponge that can efficiently adsorb rare earth ions in acidic wastewater, as well as its products and applications. In the preparation process, cheap and green β-cyclodextrin (β-CD), polyvinyl alcohol (PVA), phosphorylated chitosan (PCS) and citric acid (CA) are used as raw materials. By mixing polyvinyl alcohol functionalized with β-cyclodextrin and phosphorylated chitosan, and using citric acid as a cross-linking agent, a cyclodextrin composite nanosponge that can be used to recover rare earth ions in acidic wastewater is successfully prepared. Among them, chitosan (CS), as a linear amino polysaccharide, contains a large number of amino groups and hydroxyl groups, and has good adsorption properties for metal ions; the phosphate group not only has a high charge density, but also according to the theory of hard and soft acids and bases, rare earth ions as hard Lewis acids have a strong binding tendency to the phosphate group; polyvinyl alcohol, as a water-soluble polyhydroxy polymer, has excellent biocompatibility and non-toxicity, and can effectively improve the stability and mechanical strength of the material; the synergistic effect of each substance enables the prepared cyclodextrin composite nanosponge to efficiently adsorb rare earth ions in acidic wastewater. The experimental results show that the composite nanosponge prepared by the present invention has good adsorption performance for Ce 3+ and Tb 3+The adsorption capacity of the composite nanosponge can reach 452.21 mg / g and 442.95 mg / g respectively, showing a high adsorption capacity; in a mixed solution containing rare earth ions and a variety of competitive ions, the composite nanosponge can absorb Ce 3+ and Tb 3+ The removal rates of 70.0% and 56.4% respectively, while the removal rates of other metal ions were less than 8%, showing efficient adsorption performance; the removal rate of the composite nanosponge was still greater than 70.4% in three adsorption-desorption cycles, and the desorption rate was higher than 81.6%, showing good recycling ability; the removal rate of the composite nanosponge for rare earth ions in simulated acidic mine water was higher than 92.9%, while the adsorption rate of competing ions did not exceed 2.0%, showing potential application prospects for the recovery of rare earth ions in acidic wastewater.
[0021] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:
[0023] Figure 1 This is a scanning electron microscope image of the composite nanosponge prepared in Example 1 for efficiently adsorbing rare earth ions in acidic wastewater;
[0024] Figure 2 The energy dispersive X-ray spectrum of the composite nanosponge prepared in Example 1 for efficiently adsorbing rare earth ions in acidic wastewater;
[0025] Figure 3 The composite nanosponge prepared in Example 1 is a diagram showing the adsorption effect of rare earth ions on acidic wastewater, wherein (a) is the adsorption effect of the composite nanosponge on rare earth ions Ce. 3+ (b) shows the adsorption effect of the composite nanosponge on rare earth ions Tb 3+ Adsorption effect diagram;
[0026] Figure 4 This is a diagram showing the recovery effect of the composite nanosponge for efficiently adsorbing rare earth ions in acidic wastewater prepared in Example 1;
[0027] Figure 5The graphs are of the cyclic regeneration performance of the composite nanosponge for efficiently adsorbing rare earth ions in acidic wastewater prepared in Example 1, wherein (a) is the adsorption graph of the composite nanosponge and (b) is the desorption graph of the composite nanosponge. DETAILED DESCRIPTION
[0028] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.
[0029] Example 1
[0030] A composite nanosponge for efficiently absorbing rare earth ions in acidic wastewater, the specific preparation method of which is as follows:
[0031] (1) At 90° C., 1 g of polyvinyl alcohol was placed in 9 mL of deionized water to fully dissolve the polyvinyl alcohol into a polyvinyl alcohol aqueous solution with a mass percentage of 10%, and then 0.5 g of β-cyclodextrin was added to the polyvinyl alcohol aqueous solution, and then stirred until a clear liquid was obtained; 2 mL of a 15% w / v sodium hydroxide aqueous solution was mixed with 1.25 mL of dimethyl sulfoxide, and then 0.4 mL of epichlorohydrin was added to form a mixed solution; 5 mL of the clear solution and 1.5 mL of the mixed solution were taken, respectively, and the mixed solution was poured into the clear solution, and then reacted at 60° C. for 3 h to obtain a polyvinyl alcohol solution grafted with cyclodextrin, and then 5 mL of the polyvinyl alcohol solution grafted with cyclodextrin was taken, 1 mL of a 15% w / v citric acid aqueous solution was added thereto, and then reacted at 80° C. for 2 h to obtain a reaction solution 1;
[0032] (2) 2.5 g of chitosan was placed in 20 mL of deionized water, and 2 mL of acetic acid was added, followed by stirring at 28° C. for 1 h to obtain a light yellow translucent solution, followed by adding 25 mL of phosphoric acid to the light yellow translucent solution, and then reacting at 55° C. for 3 h to obtain a light brown liquid, and then the light brown liquid was slowly poured into 100 mL of anhydrous ethanol to form a precipitate, and the precipitate was centrifuged at 8000 rpm for 10 min, and then washed with ethanol 3 times to obtain phosphorylated chitosan;
[0033] (3) 1 g of the phosphorylated chitosan prepared in step (2) was placed in 10 mL of deionized water, 100 μL of acetic acid was added until the solution became viscous, and then 1 mL of 15% w / v citric acid aqueous solution was added, and the mixture was reacted at 80° C. for 3 h to obtain reaction solution 2;
[0034] (4) The reaction solution 1 prepared in step (1) and the reaction solution 2 prepared in step (3) are mixed in a volume ratio of 1:1, and then stirred at room temperature for 0.5 h. After the stirring, a 1 mol / L sodium hydroxide aqueous solution is added at a rate of 1 drop per second to obtain a bead-like material. After standing overnight, the bead-like material is taken out and freeze-dried at -18°C for 20 h to obtain a composite nanosponge that efficiently adsorbs rare earth ions in acidic wastewater.
[0035] Performance Testing
[0036] 1. Scanning electron microscopy characterization of the composite nanosponge prepared in Example 1 for efficient adsorption of rare earth ions in acidic wastewater
[0037] like Figure 1 As shown, the composite nanosponge has a large number of evenly distributed micropores, and these micropore structures are in the form of an open honeycomb three-dimensional network.
[0038] 2. Energy dispersive X-ray spectroscopy characterization of the composite nanosponge prepared in Example 1 for efficient adsorption of rare earth ions in acidic wastewater
[0039] Table 1 Element content analysis of the composite nanosponge for efficient adsorption of rare earth ions in acidic wastewater prepared in Example 1
[0040]
[0041] like Figure 2 As shown in Table 1, by comparing the distribution and percentage of carbon (C), oxygen (O), nitrogen (N) and phosphorus (P) elements in the test samples, it can be seen that the C, O, N and P elements of the composite nanosponge are evenly distributed, and the total content of O, N and P is close to 86%. The high content of these elements also proves the wide distribution of active sites in the material, which provides evidence for the phenomenon of higher adsorption capacity in subsequent adsorption experiments.
[0042] 3. Explore the adsorption and recovery effects of the composite nanosponge for rare earth ions in acidic wastewater prepared in Example 1
[0043] (1) Adsorption effect
[0044] Cerium nitrate hexahydrate and terbium nitrate hexahydrate were dissolved in distilled water to prepare a 1000 mg / L standby solution, and then the standby solution was diluted to obtain two working solutions of different concentrations. The composite nanosponge prepared in Example 1 was mixed with the above two working solutions of different concentrations for 10 hours to explore the effect of the composite nanosponge on Ce in the working solution with a concentration range of 15 to 250 mg / L. 3+ and Tb 3+ The maximum adsorption capacity and selective adsorption performance of Figure 3 (a) and Figure 3 As shown in (b). It can be seen from the figure that the composite nanosponge has 3+ and Tb 3+ The maximum adsorption amounts are 452.21 mg / g and 442.95 mg / g respectively.
[0045] (2) Recovery effect
[0046] The composite nanosponge was used to recover rare earth ions in simulated acid mine water at 25°C and pH 6.5. The simulated acid mine water contained the following ions: 4.12 mg / L Ce 3+ 、1.64mg / LEu 3+ , 1.74mg / LTb 3+ 、36.53mg / L Na + , 41.19mg / LK + 、254.70mg / L Ca 2+ and 148.00mg / L Mg 2+ The recovery ability of the composite nanosponge for rare earth ions in the simulated acidic wastewater experiment is as follows: Figure 4 As shown, from Figure 4 It can be seen that the removal rate of rare earth ions is higher than 92.9%, while the adsorption rate of competitive ions does not exceed 2.0%.
[0047] 4. Exploring the recycling performance of the composite nanosponge prepared in Example 1 for efficient adsorption of rare earth ions in acidic wastewater
[0048] In order to explore the reusability of the composite nanosponge prepared in Example 1, 7 mg of the composite nanosponge was put into 10 mL of a mixed aqueous solution of cerium nitrate hexahydrate and terbium nitrate hexahydrate with a concentration of 20 mg / L, and then shaken at 25°C and 120 r / min for 4 h. The adsorbed composite nanosponge was placed in the eluent for desorption for 4 h using 0.05 mol / L hydrochloric acid as the eluent, and the above adsorption-desorption operation was repeated 3 times. The results of the cyclic regeneration were as follows: Figure 5 (a) and Figure 5As shown in (b), after three cycles, the removal rate of rare earth ions by the composite nanosponge is still greater than 70.4%, and the desorption rate is higher than 81.6%.
[0049] In summary, the present invention provides a method for preparing a composite nanosponge that efficiently adsorbs rare earth ions in acidic wastewater, as well as its products and applications. The composite nanosponge is prepared from cheap and green β-cyclodextrin, polyvinyl alcohol, phosphorylated chitosan and citric acid as raw materials, by mixing polyvinyl alcohol functionalized with β-cyclodextrin and phosphorylated chitosan, and using citric acid as a cross-linking agent. By exploring the adsorption effect of the composite nanosponge on rare earth ions, the recovery effect of rare earth ions in simulated acidic mineral water, and the recycling performance, it is confirmed that the composite nanosponge has great application prospects for the recovery of rare earth ions in acidic wastewater.
[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a composite nanosponge for efficiently adsorbing rare earth ions in acidic wastewater, characterized in that: The preparation method is as follows: (1) adding β-cyclodextrin to a polyvinyl alcohol aqueous solution, and then stirring to obtain a clear liquid; mixing a sodium hydroxide aqueous solution with dimethyl sulfoxide, and then adding epichlorohydrin to form a mixed liquid; pouring the mixed liquid into the clear liquid, and then reacting at 60 to 65° C. for 3 to 4 hours to obtain a polyvinyl alcohol solution grafted with cyclodextrin, and then adding a citric acid aqueous solution to the polyvinyl alcohol solution grafted with cyclodextrin, and then reacting at 75 to 80° C. for 2 to 3 hours to obtain a reaction solution 1; (2) placing phosphorylated chitosan in deionized water, then adding acetic acid until the solution becomes viscous, then adding citric acid aqueous solution, and reacting at 75-80° C. for 3 h to obtain reaction solution 2; (3) The reaction solution 1 in step (1) and the reaction solution 2 in step (2) are mixed in a volume ratio of 1:1, and then stirred at room temperature for 0.5 to 1 hour. After the stirring, a 1 mol / L sodium hydroxide aqueous solution is added dropwise to obtain a bead-like material. After standing overnight, the bead-like material is taken out and freeze-dried at -18°C for 16 to 24 hours to obtain a composite nanosponge that efficiently adsorbs rare earth ions in acidic wastewater.
2. The preparation method according to claim 1, characterized in that: The mass percentage of polyvinyl alcohol in the polyvinyl alcohol aqueous solution in step (1) is 10%; the mass ratio of polyvinyl alcohol to β-cyclodextrin in the polyvinyl alcohol aqueous solution is 1:0.
5.
3. The preparation method according to claim 1, characterized in that: The concentration of the sodium hydroxide aqueous solution in step (1) is 15% w / v; the volume ratio of the sodium hydroxide aqueous solution, dimethyl sulfoxide and epichlorohydrin is 2:1.25:0.
4.
4. The preparation method according to claim 1, characterized in that: In step (1), the volume ratio of the mixed solution to the clarified solution is 0.3:1; the concentration of the citric acid aqueous solution is 15% w / v; and the volume ratio of the cyclodextrin grafted polyvinyl alcohol solution to the citric acid aqueous solution is 5:
1.
5. The preparation method according to claim 1, characterized in that: The preparation method of the phosphorylated chitosan in step (2) is as follows: chitosan is placed in deionized water, acetic acid is added, and then stirred at 25-30° C. to form a light yellow translucent solution, phosphoric acid is then added to the light yellow translucent solution, and then the solution is reacted at 50-55° C. for 3-3.5 hours to obtain a light brown liquid, and then the light brown liquid is slowly poured into anhydrous ethanol to form a precipitate, and the precipitate is centrifuged and washed with ethanol to obtain phosphorylated chitosan.
6. The preparation method according to claim 5, characterized in that: The mass volume ratio of the chitosan, deionized water, acetic acid and phosphoric acid is 2.5:20:2:25, g:mL:mL:mL.
7. The preparation method according to claim 1, characterized in that: The mass volume ratio of the phosphorylated chitosan, acetic acid and citric acid aqueous solution in step (2) is 1:100:1, g:μL:mL; the concentration of the citric acid aqueous solution is 15% w / v.
8. The preparation method according to claim 1, characterized in that: The dripping speed in step (3) is 1 drop per second.
9. A composite nanosponge for efficiently absorbing rare earth ions in acidic wastewater, prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the composite nanosponge for efficiently adsorbing rare earth ions in acidic wastewater according to claim 9 in recovering rare earth ions.
Citation Information
Cited By
Polymer resin for removing metal impurities in cyanide-free electroplating cadmium solution as well as preparation method and use method of polymer resin
CN120441878A
A polymer resin for removing metal impurities in a cyanide-free electroplating cadmium solution and a preparation method and use method thereof
CN120441878B
PQQ-Stabilizing Nanosponge-Based Composition and Method for Preparingthe Same
KR103010958B1